2019
DOI: 10.1523/eneuro.0358-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

“Females Are Not Just ‘Protected’ Males”: Sex-Specific Vulnerabilities in Placenta and Brain after Prenatal Immune Disruption

Abstract: Current perceptions of genetic and environmental vulnerabilities in the developing fetus are biased toward male outcomes. An argument is made that males are more vulnerable to gestational complications and neurodevelopmental disorders, the implication being that an understanding of disrupted development in males is sufficient to understand causal mechanisms that are assumed to be similar but attenuated in females. Here we examine this assumption in the context of immune-driven alterations in fetal brain develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 73 publications
5
49
0
Order By: Relevance
“…For example, male placenta weight was significantly greater than female placenta weight (Table 2 , Fig. 3 ), consistent with prior studies [ 19 21 ]. Importantly, the statistical significance of this measure increased after correcting for litter-to-litter variation.…”
Section: Main Textsupporting
confidence: 90%
“…For example, male placenta weight was significantly greater than female placenta weight (Table 2 , Fig. 3 ), consistent with prior studies [ 19 21 ]. Importantly, the statistical significance of this measure increased after correcting for litter-to-litter variation.…”
Section: Main Textsupporting
confidence: 90%
“…Indeed, epidemiological studies on perinatal adverse outcomes [60][61][62] or the emergence of psychiatric disorders such as ASD [63], schizophrenia [64,65], and attention deficit hyperactivity disorder [66] have revealed an imbalanced male-tofemale ratio with stronger symptoms in males. However, recent work also revealed that females have their own plethora of deleterious manifestations [67][68][69], warning against the extrapolation of male disease mechanisms to females. Interestingly, our results are in accordance with this view, with males exhibiting stronger symptoms than females, and males and females having dissimilar deficits following birth modifications in behavioral patterns such as the ultrasonic vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Autism spectrum disorders (ASD) is a behaviourally defined heterogeneous complex of neurodevelopmental conditions characterized by persistent deficient social interaction, impaired communication as well as restricted or stereotyped patterns of behaviours, interests and activities, and abnormalities in sensory reactivity [ 1 , 2 ]. Epidemiological studies estimate that roughly 1% of the world’s population is thought to have an ASD, but exact numbers are highly dependent upon the still-evolving methodology [ 3 , 4 , 5 ]. A significant rise in the prevalence of the condition in recent years has increased the importance of clarifying its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%